Pengaruh Flash Sale, Promo Gratis Ongkos Kirim, dan Electronic Word of Mouth Terhadap Keputusan Pembelian Produk Skintific Melalui E-Commerce Shopee di Kota Batam - zahri, Nadila jannatul; Luthfi, Andi Mulyadi; Windayati, Diana Titik (Zona Manajerial: Program Studi Manajemen (S1), 2024)
The purpose of this research is to determine and analyze the influence of Flash Sales, Free Shipping Promos, and Electronic Word of Mouth on Purchase Decisions for Skintific Products via Shopee E-commerce in Batam City. This studies employs quantitative tactics. The populace in this exam is individuals in Batam city however it's far commonplace that now not every considered one of them use Skintific gadgets, so the population for this exploration is considered as obscure. the instance for this exam was ninety six respondents. This examine tested the validity and reliability of a questionnaire because the method of facts series. The Classical Assumption check, multiple Linear Regression, speculation checking out (t and F checks), and Coefficient of determination are applied in this approach of statistics analysis for studies. statistics managing in this exam applied the SPSS programming application variant 26. The effects of this examination show that flash sale and free shipping promotions to some diploma meaningfully affect shopping for alternatives for Skintific gadgets thru Shopee internet based business, yet digital conversation to a few diploma makes no certain difference. important impact on the choice to buy Skintific items via Shopee net business. there's a concurrent tremendous and huge impact on streak deals, loose transportation promotions, and electronic casual change on buying choices for skintific objects thru Shopee internet primarily based enterprise in Batam city.